Pengaruh Waktu Tunggu Terhadap Kepuasan Pasien pada Pemeriksaan USG di RSU Kertha Usada Buleleng - Febry Ivone Mamun; Cokorda Istri Ariwidyastuti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to analyze the effect of waiting time on patient satisfaction undergoing ultrasound examinations at Kertha Usada Buleleng General Hospital. A quantitative survey method was employed, involving 50 respondents. Data were collected using a questionnaire measuring waiting time and patient satisfaction levels. The results indicate that the average waiting time is 90 minutes, and there is a significant negative correlation between waiting time and patient satisfaction (r = -0.58, p < 0.05). Approximately 80% of patients reported being satisfied or sufficiently satisfied, while 20% expressed dissatisfaction. The study concludes that improved management of waiting times and enhanced service quality are essential for increasing patient satisfaction. Recommendations for the hospital include developing a more efficient waiting time management system and improving communication with patients.